Analysis of Sectoral and Spatial Linkages for Regional Development in Riau Islands Province - Sri Wahyuni; Hermanto Siregar; Ernan Rustiadi; Andrea Emma Pravitasari (Indonesian Journal of Geography, 2026)
Planning for sustainable development needs to be based on a region’s potential and suitable methods for determining appropriate policies. Therefore, this study aimed to identify key sectors and analyze the linkages of sectors and regions in Riau Island Province. The secondary data used were from Indonesia’s 2016 Input-Output (IO)/Inter-Regional Input-Output (IRIO) table compiled by the Central Bureau of Statistics. This table provides information on the potential of sectors and regional interdependence. The results showed that the key sectors were the Processing Industry, Electricity and Gas Procurement, Wholesale and Retail Trade, Accommodation and food services, as well as Information and Communication. The composition of exports and imports of the Riau Islands involved other regions, most of which were dominated by neighboring provinces. In addition, the economy in the Riau Islands was influenced by final demand shocks from different provinces, namely Riau, South Sumatra, North Sumatra, and Lampung, which are still in the Sumatra islands. This showed how location closeness affected the local economy. The lack of connectivity between the islands suggested a need for government initiatives to enhance transportation accessibility. In addition, the archipelago's maritime capabilities are crucial for industrial potential, but environmental impact needs to be considered for its sustainability.Received: 2025-02-18 Revised: 2025-12-17 Accepted: 2026-03-12 Published: 2026-04-29